Peripheral T-Cell lymphoma, not otherwise specified. Clinical-pathological study in a cohort of peruvian patients - Barrionuevo, Carlos (2019)
Objectives. The latest WHO classification of hematopoietic and lymphoid neoplasms considers 29 mature T and NK cell lymphomas. One of these corresponds to peripheral T-cell lymphoma, without another specification (LCTP-NOS). The objective of this research was to evaluate the clinical-pathological characteristics of this disease and its association with EBV infection in relation to global survival (OS). Methods. 65 cases with a diagnosis of LCTP-NOS were studied at the National Institute of Neoplastic Diseases in a period of 6 years. Clinical-pathological characteristics were evaluated, and OS and other clinical parameters were compared between cases with infection and without EBV infection. Results. There were (45 %) positive cases for EBV. The average age was 50 years and (29 %) were women. The proportion of patients with and without B symptoms was similar. The stages were usually advanced, with elevated lactate dehydrogenase. The international prognostic index was intermediate-high or high in most cases. The OS in all cases at 5 years was an average of (29,4 %). In general, the response to chemotherapy treatment was poor. Although positive EBV cases had worse OS than negative EBVs, the difference was not statistically significant. There was a significant difference for B symptoms, being more frequent in EBV positive cases. There was also a statistically significant difference in OS at three years between positive LCTP-NOS EBV with cytotoxic phenotype vs those without cytotoxic phenotype. Conclusions. LCTP-NOS is a malignancy with a poor prognosis, with low OS and poor response to chemotherapy treatment. For a better assessment of EBV infection as a prognostic factor, the amount and type of infected lymphocytes should be considered